Challenges of lawyer profesional ethics in the age of legal artificial intelligence - Solar Cayón, José Ignacio (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2021)
The development of legal artificial intelligence is bringing about substantial changes in the practice of law that pose huge deontological challenges. One of the most important is building a universal deontology, capable of giving efficient answers to an increasingly globalized legal market. Furthermore, the irruption of legaltech companies that provide automated legal services is promoting a liberalization of the legal market that reveals the inadequacies of the deontological approach and calls for a new regulatory scheme of legal services. Finally, the article shows the potential of legal artificial intelligence to dissolve some basic categories of the deontology of legal profession, as well as the impact of certain AI tools on some lawyer’s ethical duties